Efektivitas Fungisida Berbahan Aktif Heksakonazol terhadap Penyakit Jamur Akar Putih Bibit Tanaman Karet (Hevea brasiliensis) - Wahyuni, Mardiana; Simanjuntak, Jenny Hotnida; Sitompul, Ingrid Ovie (Agrotekma: Jurnal Agroteknologi dan Ilmu Pertanian, 2018)
White Root Fungus Disease (JAP) is the biggest threat in rubber. The attack can result in a significant reduction in number, especially in plants lasting 0-3 years. The pathogen that causes white fungus is Rigidoporus lignosus. In JAP endemic areas, decreased tree density 40-50%. In rubber seedlings, symptoms of JAP attack with yellowing color leaves, then dry and fall. This study was conducted at STIP-AP Medan from January 2017 to June 2017. The aim of the study was to determine the effectiveness of several doses of hexaconazole. This study uses a non-factorial Randomized Block Design (RBD) with four replications. Hexaconazole fungicides are active with treatment of A0, A1, A2, A3 and A4 (0, 5, 10, 15 and 20 ml / l air). The results of this study indicate that A2 application of hexaconazole-active fungicides (10 ml / l air) has been effective in controlling JAP disease in rubber seedlings.